Dealing with hydrologic data scarcity: the case of the Tindouf basin - Gonçalvès, Julio; Nutz, Alexis; Séraphin, Pierre; Chekireb, Amine; Kabiri, Lahcen; Deschamps, Pierre (Comptes Rendus. Géoscience)
This study proposes a first conceptual model for the hydrogeological functioning of the Tindouf Aquifer System (TAS) building upon geomorphological, geological and hydrological remotely sensed and ground observations. Exploratory sketches of the piezometric contours for the main aquifers of the TAS identified (i) recharge areas on the Anti-Atlas relief and the Hamada plateau, (ii) and discharge areas mainly located in the southeastern region where countless salt pans associated with groundwater evaporation were observed. The latter confirms a chiefly endorheic functioning of the TAS. A basin-scale groundwater balance based on gravity data from the Gravity Recovery And Climate Experiment (GRACE) was established to estimate values of the different terms of the hydrogeological water budget of the TAS. A recharge at $0.8± 0.2$ mm${· }$yr$^{-1}$, an evaporation at $0.9± 0.2$ mm${· }$yr$^{-1}$ and GRACE-derived groundwater depletion at $-0.7± 0.1$ mm${· }$yr$^{-1}$ due to pumping and evaporation in excess of lateral groundwater flow are obtained.